1987
DOI: 10.1037/0097-7403.13.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying retarded emergence of conditioned responding following inhibitory training: Evidence for the comparator hypothesis.

Abstract: The comparator hypothesis posits that conditioned responding is determined by a comparison at the time of testing between the associative strengths of the conditioned stimulus (CS) and stimuli proximal to the CS at the time of conditioning. The hypothesis treats all associations as being excitatory and treats conditioned inhibition as the behavioral consequence of a CS that is less excitatory than its comparator stimuli. Conditioned lick suppression by rats was used to differentiate four possible sources of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…That is, in the absence of the training context, the b process (or activation of the CS into A2, according to SOP) should not have been anticipatory to CS onset. Of note, we used highly distinct contexts that extensive prior research in our laboratory has demonstrated are well discriminated by rats (e.g., Laborda, Witnauer, & Miller, 2011;Schachtman et al, 1987). OPT and SOP predict the PPD effect only if testing is conducted in the same context where training was conducted, a prediction that received support in Experiment 2, but only when the spacing of trials during training was large.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, in the absence of the training context, the b process (or activation of the CS into A2, according to SOP) should not have been anticipatory to CS onset. Of note, we used highly distinct contexts that extensive prior research in our laboratory has demonstrated are well discriminated by rats (e.g., Laborda, Witnauer, & Miller, 2011;Schachtman et al, 1987). OPT and SOP predict the PPD effect only if testing is conducted in the same context where training was conducted, a prediction that received support in Experiment 2, but only when the spacing of trials during training was large.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in the control condition (Groups 5C and 50C) experienced one daily 5-min exposure to the training context in order to equate subjects for overall handling and retention interval between training and testing. These 5 min of exposure were not expected to have a large impact on the PPD, on the basis of prior research in our laboratory (Schachtman, Brown, Gordon, Catterson, & Miller, 1987) that indicated that at least 480 min of context extinction is necessary for observing retrospective revaluation based on posttraining context extinction.…”
Section: Subjects and Apparatusmentioning
confidence: 99%
“…Similarly, the Same cue in Group Down of Experiment 3 (equivalent to Group 5 of Experiment 4) showed reliable excitation in Test 1 and marginal inhibition in Test 2. Holland (1984a) and Schachtman, Brown, Gordon, Catterson, and Miller (1987) have noted other examples of cues simultaneously possessing excitatory and inhibitory powers.…”
Section: Discwsionmentioning
confidence: 99%
“…As a result, the context-illness association should extinguish and less retrieval interference would be present to suppress the taste-illness association. This idea is conceptually sim-ilar to the "comparator hypothesis," which is based on the premise that the conditioned response is determined by the comparisons of the current associative strengths of the CS and any other stimuli that were present at conditioning (e.g., Kasprow, Schachtman, & Miller, 1987;Matzel, Schachtman, & Miller, 1985;Matzel, Shuster, & Miller, 1987;Schachtman, Brown, Gordon, Catterson, & Miller, 1987).…”
Section: Groups R48 R72mentioning
confidence: 99%